1995
DOI: 10.1002/chin.199546203
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Improvement in the Synthesis of Epibrassinolide.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Melting points were measured on a Kofler block. 24-Epicastasterone (1) and 24-epibrassinolide (6) were synthesized by the literature method [5]. Electronic absorption spectra of solutions of the studied compounds were recorded on a Cary-500 spectrophotometer.…”
Section: Methodsmentioning
confidence: 99%
“…Melting points were measured on a Kofler block. 24-Epicastasterone (1) and 24-epibrassinolide (6) were synthesized by the literature method [5]. Electronic absorption spectra of solutions of the studied compounds were recorded on a Cary-500 spectrophotometer.…”
Section: Methodsmentioning
confidence: 99%
“…The resulting oil was mixed with water and extracted with CHCl 3 . The organic layer was dried over Na 2 SO 4 H 3 ](22R,23R,24R)-24-Methy-5a-cholest-2-en-6-on-22,23-diol (10) Diacetate 9 (58 mg, 0.112 mmol) was dissolved in a solution of KOH in MeOH (5%, 3 ml). The mixture was heated under reflux for 1 h, then cooled down and acidified by adding a mixture AcOH-MeOH (1:4) to reach pH 7.…”
Section: Methodsmentioning
confidence: 99%
“…[2][3][4] As a result, now it is the most practically useful compound of this group; for a number of years preparations with 24-epibrassinolide ( Figure 1) as an active ingredient have been used in agriculture. 5,6 Research in the recent years has revealed its potential usefulness in medicine also.…”
Section: -Epibrassinolide Holds a Special Place Among Natural Brassmentioning
confidence: 99%
“…The compounds were synthesized by the literature methods [3,4]. * Samples were prepared for the study by triturating with anhydrous finely dispersed KBr and pressing in vacuo.…”
mentioning
confidence: 99%